The assembly : a spirituality - Lathrop, Gordon W., 1939- (Fortress Press, 2022)
In his previous book, The Pastor: A Spirituality, Gordon W. Lathrop writes: "The most important symbol of Christ in the room is not the minister, not the altar, not even the bread and wine or the water of the font. It is the assembly, the Body of Christ, as the New Testament says" (page 27). This statement forms the central theme of this new book. Reflecting on the recent painful time of pandemic, when the wisest and most caring course was not to assemble at all, has illuminated the author's conviction and strengthened it. But as churches return to in-person worship and life in community, they will need to revisit formation in assembly practice. This book articulates why and how the assembly is so important in Christianity. Lathrop intends the book to assist Christian congregations and their pastors or priests to recover vital, participatory, and life-giving in-person worship after the pandemic. He further intends that participants will see and treasure the importance of assembly as the primary form of "church" and as a vital source of Christian daily life. Part 1 of the book looks in depth at the assembly, discusses why the sacraments are assembly events, and explores how the assembly forms Christians for daily living. Part 2 presents a critical catechism for the assembly, with emphasis on the sacraments, the Lord's Prayer, the Creed, and the Ten Commandments.